ANALISIS KUALITAS VOIP PADA SCTP YANG MENGGUNAKAN EXPLICIT CONGESTION NOTIFICATION (ECN) DAN ACTIVE QUEUE MANAGEMENT (AQM) - , La Surimi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
VoIP application is growing rapidly along with the development of Internet network technology. VoIP applications is the real time applications that its services are highly dependent on the quality of delay and jitter, which it is difficult to be met by protocol that has reliable data transfer feature and congestion control such as TCP. On the other hand the use of UDP that has no congestion control make chance of causing congestion in the network is very large. The use of SCTP as an alternative protocol was also not able to accommodate the strengths and weaknesses of TCP and UDP. Some research shows that repairs or modifications to the SCTP congestion control mechanism is needed. The Use of Explicit Congestion Notification mechanism (ECN) and Active Queue Management (AQM) in some studies show that these two mechanisms can reduce delay and jitter values. This study tested and analysis the quality of VoIP over SCTP with ECN and one kind of AQM mechanism that is AVQ, in network simulator NS2. Simulations carried out by independent replication technique. In the nonideal network scenario where the network latency is very high and bandwidth is very low, Wilcoxon Signed Rank Test with 5% sigificance level (c=(1,96) show significant different between VoIP quality (MOS) on SCTP plus ECN+AVQ and VoIP quality on SCTP without ECN+AVQ. with the value of the test statistic is greater than the value of c ,that is 2.82 and 2.05. This study also did comparison of SCTP MOS VoIP call that uses ECN and AVQ with MOS values VoIP calls using the TCP, and UDP protocols. The result SCTP with ECN and AVQ outperform TCP with statistical test value greater than the value of c in all network conditions, namely 2.80, 2.67, 2.80 and 2.80, but can not surpass UDP yet with the value of a statistical test greater then value of c in the three scenarios (high bandwidth low latency, high bandwidth and low latency high bandwidth low latency), namely, 2,50, 2.74, and 2.80. Keywords : VoIP, SCTP, Explicit Congestion Notification (ECN), Active Queue Management (AQM), Adaptive Virtual Queue (AVQ).